Comparative Analysis of WRKY Genes Potentially Involved in Salt Stress Responses in Triticum turgidum L. ssp. durum - Yousfi, Fatma-Ezzahra; Makhloufi, Emna; Marande, William; Ghorbel, Abdel W.; Bouzayen, Mondher; Bergès, Hélène (Frontiers in Plant Science, 2017)
WRKY transcription factors are involved in multiple aspects of plant growth, development and responses to biotic stresses. Although they have been found to play roles in regulating plant responses to environmental stresses, these roles still need to be explored, especially those pertaining to crops. Durum wheat is the second most widely produced cereal in the world. Complex, large and unsequenced genomes, in addition to a lack of genomic resources, hinder the molecular characterization of tolerance mechanisms. This paper describes the isolation and characterization of five TdWRKY genes from durum wheat (Triticum turgidum L. ssp. durum). A PCR-based screening of a T. turgidum BAC genomic library using primers within the conserved region of WRKY genes resulted in the isolation of five BAC clones. Following sequencing fully the five BACs, fine annotation through Triannot pipeline revealed 74.6% of the entire sequences as transposable elements and a 3.2% gene content with genes organized as islands within oceans of TEs. Each BAC clone harbored a TdWRKY gene. The study showed a very extensive conservation of genomic structure between TdWRKYs and their orthologs from Brachypodium, barley, and T. aestivum. The structural features of TdWRKY proteins suggested that they are novel members of the WRKY family in durum wheat. TdWRKY1/2/4, TdWRKY3, and TdWRKY5 belong to the group Ia, IIa, and IIc, respectively. Enrichment of cis-regulatory elements related to stress responses in the promoters of some TdWRKY genes indicated their potential roles in mediating plant responses to a wide variety of environmental stresses. TdWRKY genes displayed different expression patterns in response to salt stress that distinguishes two durum wheat genotypes with contrasting salt stress tolerance phenotypes. TdWRKY genes tended to react earlier with a down-regulation in sensitive genotype leaves and with an up-regulation in tolerant genotype leaves. The TdWRKY transcripts levels in roots increased in tolerant genotype compared to sensitive genotype. The present results indicate that these genes might play some functional role in the salt tolerance in durum wheat.